Taming the Great Desert: Adam in the prehistory of Oman - Gernez, Guillaume; Giraud, Jessica (Archaeopress, 2019)
Located at the margins of the Rub Al-Khali desert, a place of interactions between settled and nomadic populations, the Adam oasis occupies a pivotal role in the history of Oman. However, almost nothing was known about its foundation and early developments. In 2006, the French Archaeological Mission in Central Oman began the exploration of the area. After ten years of field research using innovative methods and technologies, much is now revealed about the importance of Adam in the prehistory and early history of Oman. This is the first monograph about the research carried out at Adam and it includes seven chapters written by specialists directly involved in the field activities. Each major period is described in detail, including evidence of Palaeolithic occupation, Neolithic settlements, Early and Middle Bronze Age necropolises, Iron Age ritual sites and also an ethnographic study of the traditional water sharing within the oasis
Keywords: Archéologie – Oman

Magan: the land of copper prehistoric metallurgy of Oman - Giardino, Claudio (Archaeopress, 2019)
Keywords: Archéologie – Oman

Messages from the past: rock art of Al-Hajar Mountains - Fossati, Angelo E. (Archaeopress, 2019)
Turtles, ibexes, ships, inscriptions ... Thousands of engraved and painted figures intrigue visitors in the wadis of Al-Hajar Mountains. Who created these enigmatic figures and when were they made? What are their hidden meanings? For the first time, this volume tries to answer these questions. It is the result of the archaeological surveys and investigations undertaken by the author over the last ten years under the patronage of the Ministry of Heritage and Culture. In this book, the author takes the reader on an in-depth journey into the various themes present in the rock art of Oman. He offers theories on the chronology and interpretation, while exploring the landscape setting of the decorated panels and how best to research these. Several beautiful photographs and scientific tracings of the rock art accompany the text. The volume closes offering to enthusiasts and tourists a series of guided visits with GPS maps to the most interesting and visible rock art sites protected by Royal Decrees of the Sultanate
Keywords: Archéologie – Oman

The first peoples of Oman: palaeolithic archaeology of the Nejd Plateau - Rose, Jeffrey I.; Hilbert, Yamandu H.; Marks, Anthony E.; Usik, Vitaly I. (Archaeopress, 2019)
In Dhofar, the southern Governorate of the Sultanate of Oman, the deep canyons cutting the Nejd plateau once flowed with perennial rivers, feeding wetland environments, forests, and grasslands across the now desiccated interior. The first peoples of Oman flourished along these waterways, drawn to the freshwater springs and abundant game, as well as the myriad chert outcrops with which to fashion their hunting implements and other tools. The landscapes of the Nejd Plateau are a natural museum of human prehistory, covered in carpets of chipped stone debris. The archaeological evidence presented in this work encompasses the cultural remains of over a million years of successive human occupations, from the Lower Palaeolithic to the Late Palaeolithic. Once considered an evolutionary backwater or merely a migratory way station, the archaeology of Dhofar requires a fundamental reconsideration of the role of Southern Arabia in the origin and dispersal of our species
Keywords: Archéologie – Oman

Projectile points of Southeastern Arabia: quantitative approach to regional issues - Maiorano, Maria Pia (2018)
Keywords: Archéologie – Oman

New prehistoric sites in the Qumayrah Valley, Oman. Preliminary results of two seasons of investigations - Bialowarczuk, Marcin (2018)
Keywords: Archéologie – Oman

Holocene Drainage and Wetland Development in the Batinah Region of Northern Oman - Parton, Ash (2018)
Keywords: Archéologie – Oman

Neolithic coastal populations from South-Eastern Arabia: the contribution of funerary and bio-anthropological data - Munoz, Olivia (2018)
Keywords: Archéologie – Oman

Ancient exploitation of coastal resources during the Arabian Neolithic: the settlements of Ra's al Hamra 6 and 5 (Sultanate of Oman) - Marrast, Anaïs (2018)
Keywords: Archéologie – Oman

First contribution of the excavation and the chronostratigraphic study of Ruways 1 Neolithic shell middens (Oman), in terms of Neolithization, palaeoeconomy, social-environmental interactions and site formation processes - Berger, Jean-François (2018)
Keywords: Archéologie – Oman

القوس والسهم قبل التاريخ في عمان : مواد الصناعة ومصادرها - الماحي, علي التجاني (أدوماتو, 2014)
Keywords: Archéologie – Oman

القوس والسهم قبل التاريخ في عمان : مواد الصناعة ومصادرها - الماحي, علي التجاني (أدوماتو, 2013)
Keywords: Archéologie – Oman

الأحجار الثلاثية فى منطقة جعلان بنى بوحسن، المنطقة الشرقية بسلطنة عمان - الجهوري, ناصر سعيد (أدوماتو, 2018)
Keywords: Archéologie – Oman

مواقع التراكمات الصدفية فى عمان: الجغرافيا أم ما قبل التاريخ - الماحي, علي التجاني (أدوماتو, 2018)
Keywords: Archéologie – Oman

Bedouins' Adaptation in Oman: An Indicator of Climate Change and Prehistory - Elmahi, Ali Tigani (أدوماتو, 2017)
Keywords: Archéologie – Oman

أصداف القواقع البحرية فى مواقع ما قبل التاريخ فى عمان: المدلول والمعنى - الماحي, علي التجاني (أدوماتو, 2015)
Keywords: Archéologie – Oman

الرسوم الصخرية في وادي الجفر بسلطنة عمان : الدلالة و المعنى - الجهوري, ناصر سعيد (أدوماتو, 2013)
Keywords: Archéologie – Oman

العصر البرونزي في الجزء الغربي من إقليم جعلان بسلطنة عمان - الجهوري, ناصر سعيد (أدوماتو, 2011)
Keywords: Archéologie – Oman

Pastorallsts Adjustment to Hematophagouse Files in Dhofar : An Analogy of an Ancient Adaptation - El-Mahi, Ali Tigani (أدوماتو, 2010)
Keywords: Archéologie – Oman

A Proposed National Archaeological Database for Oman " NADO" - Al Belushi, Mohammad Ali K. (أدوماتو, 2012)
Keywords: Archéologie – Oman

Along the aroma and spice routes : The harbour of Sumhuram, its territory and the trade between the Mediterranean, Arabia and India - Avanzini, Alessandra (Bandecchi & Vivaldi, 2011)
Keywords: Archéologie – Oman

Archaeological investigations of the Early Bronze Age burial site QA1 at Wadi al-Fajj in northern Oman: Results of the 2016 season - Rutkowski, Łukasz (Polish Archaeology in the Mediterranean, 2018)
The first excavation season of a joint project of the PCMA and Department of Archaeology and Excavations, Ministry of Heritage and Culture, Oman, was carried out in the microregion of Qumayrah in the fall of 2016. A single tomb was investigated at an Umm an-Nar period burial site in the area of the village of Al-Ayn. A complete ground-plan was traced, identifying the tomb as an example of a well-known type with interior divided into four burial chambers by crosswalls. The excavated quadrant yielded commingled skeletal remains and mortuary gifts: numerous beads, a number of pottery sherds and a single complete vessel, a few metal objects and a score of stone vessel fragments.
Keywords: Archéologie – Oman

Preliminary report on a new prehistoric site in northern Oman (Qumayrah/Ayn 2) - Białowarczuk, Marcin (Polish Archaeology in the Mediterranean, 2018)
This paper reports briefly on the results of a short reconnaissance at the site of Qumayrah–Ayn 2 (QA 2), a new prehistoric site located in a poorly studied part of the Qumayrah Valley in northern Oman. A survey and limited probing by the Omani–Polish Qumayrah Archaeological Project confirmed the presence of a sediment, approximately 15–20 cm thick, which yielded not just lithics, but also stone installations discovered in situ. One of these installations was evidently a hearth, the other a kind of platform. The lithic assemblage is characterized by a prevalence of flake technology with rare blade products. Predominant in the tools group are side-scrapers, notches and perforators produced by direct-scaled retouch. The most characteristic tools are tanged projectile points made on flakes. The main problem is contextualizing these materials. On the grounds of certain premises they may be associated with the Fasad technocomplex, but not necessarily the pre-Neolithic one as is the case of the classic types. However, a much later chronology is also quite possible.
Keywords: Archéologie – Oman

Second season of prehistoric investigations in the Qumayrah Valley, Oman - Białowarczuk, Marcin; Szymczak, Agnieszka (Polish Archaeology in the Mediterranean, 2018)
In the second field season of the Omani–Polish Qumayrah Archaeological Project, the prehistoric leg of the team conducted investigations of previously discovered lithic sites in the vicinity of Al-Ayn village. This paper summarizes the results of archaeological testing at three open campsites codenamed Qumayrah-Ayn (QA) 2, QA 6 and QA 12. The investigations provided new evidence of intensive Stone Age settlement of the Qumayrah Valley (also known as Wadi Fajj). The data, comprising lithic tools and some shell and stone beads, indicate that the occupation of these sites should be dated to various stages of the Neolithic period.
Keywords: Archéologie – Oman

By land and by sea: a history of South Arabia before Islam recounted from inscriptions - Avanzini, Alessandra ("L'Erma" di Bretschneider, 2016)
Keywords: Archéologie – Oman

Sumhuram: the becoming of the town: Khor Rori Report 4 - Buffa, Vittoria ("L'Erma" di Bretschneider, 2019)
Keywords: Archéologie – Oman

A cosmopolitan city on the Arabian coast: the imported and local pottery from Khor Rori: Khor Rori report 3 - Pavan, Alexia ("L'Erma" di Bretschneider, 2017)
Keywords: Archéologie – Oman

The urban shrine in quarter A at Sumhuram: stratigraphy, architecture, material culture - Pavan, Alexia; Degli Esposti, Michele ("L'Erma" di Bretschneider, 2016)
Keywords: Archéologie – Oman

High places in Oman: the IMTO excavations of Bronze and Iron Age remains on Jabal Salut - Condoluci, Chiara; Degli Esposti, Michele ("L'Erma" di Bretschneider, 2015)
Keywords: Archéologie – Oman

In the heart of Oman: the castle of Salut - Avanzini, Alessandra ("L'Erma" di Bretschneider, 2015)
Keywords: Archéologie – Oman

Husn Salut and the Iron Age of South East Arabia: excavations of the Italian mission to Oman 2004-2014 - Avanzini, Alessandra; Degli Esposti, Michele ("L'Erma" di Bretschneider, 2018)
The ancient oasis of Salut, located on the desert's fringes in the heart of the Oman Peninsula, not far from the modern cities of Nizwa and Bahla, is distinguished by its rich archaeological landscape, which the Italian Mission to Oman has been investigating for more than ten years. The impressive Iron Age site of Husn Salut was the focus of the coeval settlement of the area, and in all likelihood it was also a key site at the regional level. Founded in the second half of the second millennium BC, Husn Salut was a place for public gatherings which also entailed a degree of rituality, an aspect enhanced by its monumental architecture, merging, as it does, with the location on top of a small hill which dominated the surrounding plain and made the site visible from the distance. Agricultural exploitation of the plain, made possible by a sophisticated water management, stood at the basis of the site' s subsistence. The site was largely abandoned after almost one millennium of continuous settlement, probably around 300 BC, with some evidence indicating a possible later date. While the investigation of the associated settlement of Qaryat Salut is just started, this book provides a general overview of the excavation at Husn Salut and its results, together with an exhaustive discussion of its material culture, with a specific attention paid to the pottery assemblage from selected, highly significant stratigraphic sequences. The site' s chronology is also specifically addressed, as an array of radiocarbon determinations, which, when considered together with the associated material culture, indicate its fundamental relevance in the discussion about the chrono-cultural phasing of the Early Iron Age of South East Arabia
Keywords: Archéologie – Oman

Mleiha et le peuplement de la péninsule d'Oman à la période Pré-Islamique Récente - Mouton, Michel (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie – Oman

Continuity and change: Iron Age oasis settlements in Oman - Häser, Jutta (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie – Oman

L'architecture domestique de l'Age du Fer (1300-300 a.C.) dans la péninsule d'Oman: quelques documents sur les villages et la culture des oasis - Córdoba, JoaquÍn MarÍa (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie – Oman

An outline of recent discoveries at Salut in the Sultanate of Oman - Avanzini, Alessandra; Phillips, Carl (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie – Oman

The Iron I-period in South-eastern Arabia - a view from Central Oman - Schreiber, Jürgen (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie – Oman

Iron Age chronology in South East Arabia and new data from Salut, Sultanate of Oman - Phillips, Carl (Eastern Arabia in the first millenium BC, 2010)
Keywords: Archéologie – Oman

On the Flexibility of Indian Ocean Sewn‐Plank Vessels: the structural performance of Jewel of Muscat - Burningham, Nick (International Journal of Nautical Archaeology, 2019)
Keywords: Archéologie – Oman

New project on Islamic ceramics from al-Balīd: chronology, technology, tradition, and provenance - Fusaro, Agnese (Proceedings of the Seminar for Arabian Studies, 2019)
A new project on the pottery has begun since excavations resumed in 2016 at the site of al-Balīd (Ẓafār), Dhofar in southern Oman. The work concentrates on the Husn, a fortified palace, in this Islamic port. The paper presents the current project on the pottery, exploring methodology, objectives, and preliminary results. The study suggests a dating for the occupational phases of the palace identified so far (fourteenth–eighteenth century AD). The examination of the ceramic material is supported by archaeometric analysis and ethnoarchaeological work on the modern Dhofari production, the latter contributing to a better understanding of the ancient manufacturing process and the transfer of knowledge. This multidisciplinary study allows an exhaustive stylistic, technological, and archaeometric characterization of the pottery, with a special focus on local wares, also proposing or revising their chronological attribution. Moreover, a provenance study is conducted, particularly to establish the origin of the abundant and diverse imports, thus identifying the regions trading with al-Balīd during different periods. Despite previous work on al-Balīd, the study of the ceramic material has never been published properly — the project aims to fill this gap. Furthermore, it is one of the few ongoing research projects on Islamic ceramics of Dhofar and present-day Oman.
Keywords: Archéologie – Oman

Historical archaeology and heritage in the Middle East - Young, Ruth (Routledge, 2019)
Landlord villages dominated Iranian land tenure for hundreds of years, whereby one powerful landlord owned the village structures, surrounding farmland, and to all intents and purposes, the village occupants themselves, a system that in some cases remained in place up to the 1979 Islamic Revolution. In Oman, mud-brick oases were home to most of the rural population right up until Sultan Qaboos came to power in 1970, and required inhabitants of mud-brick houses to relocate into new concrete block buildings. Historical Archaeology and Heritage in the Middle East explores these everyday, rural communities in Iran and Oman in the 19th and 20th centuries, through a combination of building analysis, excavation, artefact analysis and ethnographic interviews. Drawing on the results of original field projects, the book considers new ways of exploring traditional lifeways, giving voice to hitherto largely ignored sections of the population, and offers new and different ways of thinking about how these people lived and what shaped their lives and the impact of major political and social changes on them. Place, memory and belonging are considered through the lens of material culture within these villages. The first of its kind, the book brings together methodologies, research questions, and themes that have never been used or addressed in the Middle East. Helping to establish historical archaeology in the Middle East and providing new ways in which the memorable, quotidian past can be exploited for its social and economic value in contemporary community and heritage developments, it is an ideal resource for students, scholars and practitioners of historical archaeology and heritage of and in the Middle East.
Keywords: Archéologie – Oman

Dhofar through the ages: an ecological, archaeological and historical landscape - Newton, Lynne S.; Zarins, Juris (Archaeopress, 2019)
Dhofar, the southern governorate of Oman, lies within a distinctive ecological zone due to the summer Southwest Monsoon. It is home to numerous indigenous succulent plants, the most famous of which is frankincense (Boswellia sacra). The region, tied in the past to both Oman and Yemen, has a long and distinguished archaeological past stretching back to the Lower Paleolithic ca. 1.5 my BP. Dhofar is also home to a distinctive people, the Modern South Arabian Languages speakers (MSAL) since at least the last 15,000 years. Ancient Zafar (Al-Habudi), now called Al-Baleed, and its successor Salalah was and is the province's largest city. From the seventh century onwards until the arrival of the Portuguese in 1504 AD Al-Baleed dominated the central southern Arabian coastline politically and economically. Archaeological surveys and excavations in the governorate, beginning in 1954, have brought to light Dhofar's ancient past
Keywords: Archéologie – Oman

Sewn Boats in Oman and the Indian Ocean - Vosmer, Tom (International Journal of Nautical Archaeology, 2019)
Keywords: Archéologie – Oman

Maritime footprints: examining the maritime cultural landscape of Masirah Island, Oman, past and present - Blue, Lucy; Al-Jahwari, Nasser Said; Staples, Eric; Giorgio, Lorena; Croce, Paolo; Ghidoni, Alessandro; Busaidi, Ayyoub Nagmoush Al; Belfioretti, Luca (Proceedings of the Seminar for Arabian Studies, 2014)
This interdisciplinary paper explores the potential of the maritime cultural landscape approach to a recent preliminary study of the island of Masirah in south-eastern Oman. Masirah Island is known for its extended occupation and rich archaeological record and in particular for its intensive use of marine resources from the Neolithic period up to the modern day. The Maritime Footprints project sets out to explore this dynamic maritime cultural landscape through a variety of methodologies. It employs a range of terrestrial and maritime archaeological survey techniques and approaches, mapping selected sites, their geographical context, and associated coastal features; it undertakes maritime ethnographic inquiry, studying the traditional boats, their use and change over time; it records oral traditions and explores memory and practice relating to the sea and maritime activities. Three case studies are identified to explore the changing maritime cultural landscape of the island from prehistory to the modern day in order to reveal a more nuanced appreciation of maritime activity, seafaring, and changing use of the marine resource over time and between the island's two geographically distinct coastlines. Essentially, this project aims to identify the maritime character of Masriah Island noting continuity and change over time and space.
Keywords: Archéologie – Oman

The "Jewel of Muscat" Project: reconstructing an early ninth-century CE shipwreck - Vosmer, Tom; Belfioretti, Lụca; Staples, Eric; Ghidoni, Alessandro (Proceedings of the Seminar for Arabian Studies, 2011)
The Jewel of Muscat Project focused on the reconstruction, based on an early ninth-century shipwreck, of a sewn-plank ship excavated in 1998-1999 off Belitung Island, Indonesia. Analysis of the surviving structure indicated that the ship was originally from the western Indian Ocean, and probably the Arabian Peninsula. The project comprehensively documented the research and construction of this vessel in Oman, and the sailing to Singapore. This paper addresses the technical aspects involved with building the 18 m vessel from the inevitably incomplete excavated remains, and compares the archaeological evidence with the modern reconstruction. It examines the methodological issues involved with creating a conceptual bridge between the fields of archaeology and ethnographic boatbuilding. The paper also provides an overview of the navigation and sailing performance of the vessel, documented by modern instruments. The project deepened our understanding of Early Islamic maritime technology and seafaring, while simultaneously documenting the ancient shipbuilding and navigation traditions of the Arabian Peninsula, which are rapidly becoming extinct.
Keywords: Archéologie – Oman

Archaeological excavations at bahla fort and great mosque - Bakri, Sultan Saif al- (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

Life and death in prehistoric oman: Insights from late neolithic and early bronze age funerary practices (4th - 3ed mill. BC) - Bortolini, Eugenio; Munoz, Olivia (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The beginning of copper metallurgy in oman - Giardino, Claudio (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

Textual sources about magan and the countries of the "Lower Sea" - Glassner, Jean-Jacques (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

Copper from oman in mesopotamia and the gulf: Chemical and isotopic studies - Hauptmann, Andreas (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The haft period in the oman peninsula: Cultural and economic changes - Jahwari, Nasser Said al- (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The archaeological heritage of oman. Exploration, conservation, restoration and public fruition - Lawati, Hassan Bin Mohammed Bin Ali al- (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The early oases of the hajar region - Orchard, Jocelyn; Orchard, Jeffery (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The UNESCO world heritage site of bat and al-ayn: Past, present, and future - Thornton, Christopher P.; Schmidt, Conrad (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

Magan: Another heartland of bronze age civilization. Conquerors of the desert, conquerors of the ocean - Tosi, Maurizio (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The ibri/Selme hoard from al-Zahirah province - 30 years after - Yule, Paul A. (The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris, 2015)
Keywords: Archéologie – Oman

The archaeological heritage of Oman: proceedings of the symposium, September 7th 2012, UNESCO Headquarter, Paris - Bakri, Sultan Saif al- (Ministry of Heritage and Culture, 2015)
Keywords: Archéologie – Oman

Archaeology in the Arabian sea: Masirah and Al Hallaniyyat Islands, Sultanate of Oman - Weisgerber, Gerd; Shanfari, Ali Ahmed Bakhit al-; Oman, Giovanni; Prange, Michael; Uerpmann, Margarethe (Ministry of Heritage and Culture, 2015)
Keywords: Archéologie – Oman

Naus and galleons in Arabia Felix. Portuguese nautical archaeology in Oman - Monteiro, Alexandre (Atas das Jornadas do mar. Novos rumos, novos desafíos, 2016)
Keywords: Archéologie – Oman

Traces of an Indian Community in the City of Sumhuram, Oman: Investigation of Materials Found during Excavations - Lischi, Silvia (Invisible cultures: historical and archaeological perspectives, 2015)
Keywords: Archéologie – Oman

الإعلان عن اكتشاف أثري جديد في صور (صحيفة أثير الإلكترونية, 2019)
العمانية - أثيرتمكنت وزارة التراث والثقافة بالتعاون مع بعثة من معهد السهول والصحراء الفرنسي من الكشف عن أثر
Keywords: Archéologie – Oman

Aux marges du désert : fouilles et prospections préhistoriques et protohistoriques à Adam (2012-2015) - Gernez, Guillaume (2015)
Les recherches archéologiques du programme régional, diachronique et thématique mené à Adam, en Oman central, seront présentées. L’accent sera porté sur la fouille des nécropoles de l’âge du Bronze et d’un ensemble probablement cultuel de l’âge du Fer.
Keywords: Archéologie – Oman

Les chantiers archéologiques à Oman - Gernez, Guillaume; Charpentier, Vincent (2014)
Keywords: Archéologie – Oman

Recent results on two campaigns of excavation in a multi-period graveyard, Adam North, Sultanate of Oman - Gernez, Guillaume; Righetti, Sabrina; Cervel, Mathilde; Goy, Julie (2012)
Keywords: Archéologie – Oman

A Neolithic settlement in the Adam area (Late 5th millennium BC, Sultanate of Oman) - Lemée, Marion; Beuzen-Waller, Tara; Fouache, Eric; Gernez, Guillaume; Giraud, Jessica (2012)
Keywords: Archéologie – Oman

High places in Oman: Bronze and Iron Age remains on Jabal Salut, Sultanate of Oman - Phillips, Carl; Condoluci, Chiara; Degli Esposti, Michele (2012)
Keywords: Archéologie – Oman

Typological and morphological characteristics of Omani dwellings: results from recent fieldwork in Barkāt al-Mawz and Izkī - Bandyopadhyay, Soumyen; Quattrone, Giamila; Reza, Mohamed Habib (2012)
Keywords: Archéologie – Oman

Omani seafaring and Omani boats - Vosmer, Tom (2011)
Keywords: Archéologie – Oman

Late Pre-Islamic Oman: the inner evidence - the outside view - Yule, Paul A. (2011)
Keywords: Archéologie – Oman

Aflaj UNESCO World Heritage Sites in Oman - Azri, Mahmood Mohamed Al- (2012)
Unesco
Keywords: Archéologie – Oman

The UNESCO World Heritage Site of Bat and Al-Ayn: Past, Present, and Future - Thornton, Christopher P. (2012)
Unesco
Keywords: Archéologie – Oman

The UNESCO World Heritage Site of Bahla: Excavations at the Fort and Great Mosque - Bakri, Sultan Saif al- (2012)
Unesco
Keywords: Archéologie – Oman

Mines, Workshops and Hoards: The Physical Testimony of a Great Copper-Producing Centre in the Past - Giardino, Claudio; Hauptmann, Andreas; Yule, Paul A. (2012)
Unesco
Keywords: Archéologie – Oman

The Early Oases of the Hajar Region: Centres of Power and Fly-wheels of Wealth - Orchard, Jeffery; Orchard, Jocelyn (2012)
Unesco
Keywords: Archéologie – Oman

Cultural and Economic Changes of Bronze Age Societies in the Oman Peninsula: A Quantitative and Qualitative Approach - Jawhari, Nasser Said al- (2012)
Unesco
Keywords: Archéologie – Oman

Evolution of Societies and Funerary Customs from Neolithic to Bronze Age in Oman Peninsula - Bortolini, Eugenio; Munoz, Olivia (2012)
Unesco
Keywords: Archéologie – Oman

Textual Sources about Magan and the Countries of the “Lower Sea” - Glassner, Jean-Jacques (2012)
Unesco
Keywords: Archéologie – Oman

Magan: Another Heartland of Bronze Age Civilization. Conquerors of the Desert, Conquerors of the Ocean - Tosi, Maurizio (2012)
Unesco
Keywords: Archéologie – Oman

The Archaeological Heritage of Oman: A Work in Progress Exploration, Conservation, Restoration and Public Fruition - Lawati, Hassan bin Mohammed bin Ali Al- (2012)
Unesco
Keywords: Archéologie – Oman

Team finds historic mosque in Oman (arabstoday, 2011)
Team finds historic mosque in Oman
Section: 248
Keywords: Archéologie – Oman

From Hunter-Gatherer Communities to Oasis Cultures: Climate Change and Human Adaptation on the Oman Peninsula - Häser, Jutta; Luedeling, Eike; Buerkert, Andreas; Schlecht, Eva (Oases of Oman : Livelihood Systems at the Crossroads, 2010)
Keywords: Archéologie – Oman

The Jewel of Muscat: reconstructing A ninth-century sewn-plank boat - Vosmer, Tom (Shipwrecked Tang Treasures and Moonsoon Winds, 2010)
Keywords: Archéologie – Oman

The incense trade during the islamic period - Maguer-Gillon, Sterenn le (Proceedings of the Seminar for Arabian Studies, 2015)
Keywords: Archéologie – Oman

Games on the seashore of Salalah: the discovery of mancala games in Dhofar, Sultanate of Oman - Charpentier, Vincent; de Voogt, Alex; Crassard, Rémy; Berger, Jean-François; Borgi, Federico; Mashani, Ali al- (Arabian Archaeology and Epigraphy, 2014)
During the 2013 ﬁeldwork of the French archaeological mission along the shores of the Arabian Sea, mancala games were discovered on the seashore of Salalah at the site of Ad-Dahariz. They are cup-hole carvings made directly into rock slabs and distributed in six distinct zones of the site. They usually consist of fourteen cup-holes aligned in two lines of seven, two supplementary holes being sometimes present on each side. They are the ﬁrst of their kind in South Arabia and can be compared to similar conﬁgurations of carved games elsewhere in Arabia, such as at Jebel al-Jassasiya, Qatar. This paper presents the potential origins of this game in the region, as well as a plausible dating of their use.
Keywords: Archéologie – Oman; Dhofar

Archaeological legislation in the Sultanate of Oman - Belushi, Mohammed Ali K. al- (International Journal of Heritage Studies, 2014)
Keywords: Archéologie – Oman

al-Maʿālim al-Athariyya li-Wilāyat Shināṣ - Khuzaymī, ʿAbd al-Raḥmān b. ʿĀmir (Shināṣ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Shināṣ Yawmay al-ithnayn wa’l-thulathā’ 11 wa-12 Dhū ‘l-Qaʿda (sic) al-muwāfiq 10 wa-11 Nūfimbir 2008, 2010)
Keywords: Archéologie – Oman

al-Maʿālim al-Athariyya wa-Madà Ta’thīrihā ʿalà ‘l-Khāriṭa al-Siyāḥiyya - Jābirī, Sulaymān b. Saʿūd b. ʿAlī al- (al-Muḍaybī ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat al-Muḍaybī Yawmay al-Aḥad wa’l-Ithnayn 21 wa-22 Dhū ‘l-Ḥijja al-muwāfiq 30 wa-31 Dīsimbir 2007, 2010)
Keywords: Archéologie – Oman

al-Maʿālim al-Athariyya li-Wilāyat Mirbāṭ - Shiḥrī, Muḥammad b. Mustahīl al- (Mirbāṭ ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Mirbāṭ Yawm al-ithnayn wa’l-thulathā’ 27-28 Shawwāl 1432 H. al-muwāfiq 26-27 Sibtimbar 2011, 2012)
Keywords: Archéologie – Oman

The development of boatbuilding technologies and typologies - Vosmer, Tom (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Maritime trade in the Bronze Age - Vosmer, Tom (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Hinterland trade and maritime networks in Oman from Iron Age to Late Antiquity (1000 BCE-630 CE) - Reddy, Anjana (Oman: a maritime history, 2017)
Keywords: Archéologie – Oman

Qalhat and Sur - Vosmer, Tom (The ports of Oman, 2017)
Keywords: Archéologie – Oman

The ancient port of Sumhuran - Avanzini, Alessandra (The ports of Oman, 2017)
Keywords: Archéologie – Oman

Qalʻat Āl Ḥammūdah wa-al-maʻālim al-ḥaḍārīyah fī Jaʻlān Banī Bū ʻAlī: dirāsah atharīyah miʻmārīyah - Sunaydī, ʻAlī Saʻīd ʻAlī (Muʼassasat al-Ruʼyā lil-Ṣiḥāfah wa-al-Nashr, 2019)
Keywords: Archéologie – Oman

Evolution of Land and Life in Oman: an 800 Million Year Story - Al Kindi, Mohammed Hilal (Springer International Publishing, 2018)
Keywords: Archéologie – Oman

Tower-Fortresses of Ancient Magan: A study of the tower-fortresses of the third millenium on the Oman Peninsula - Botan, Sam A. (Leiden University, 2013)
The tower-fortress on the Oman Peninsula have always been a mystery to archeologists. A total of 15 tower-houses have been excavated or surveyed by archeologists in the past decades and yet their purpose inside the settlements is still poorly understood. This thesis analyzes and evaluates the existing theories about the tower-houses and offers an alternative theory by taking into account the locations, sizes and construction techniques of these buildings, using the survey and excavation rapports. The origins of the tower-fortresses can be found as early as the end of the fourth millennium B.C., when the settlement pattern on the Oman Peninsula shifts from the coast to the hinterland. The shift from the coast to the oasis brought a diversification of resources as well as a tighter appropriation of space. Combined with an increase in the copper trade at the beginning of the third millennium, this induced more complexity in the social system. The form of social organization which emerged on the Oman Peninsula due to these factors, was one which was in a liminal stage between a chiefdom and a state society, called a stratified non-state society. The tower-fortress of the Oman Peninsula functioned in such a society as dwellings and locus of regional power of a particular family or moiety. The few towers that have been excavated show many similarities, such as: he positioning of the towers within the settlements, the usage of a platform on which the towers rest, the interior of the platform consisting of two rows of chambers divided by a corridor or well, the ditches surrounding the towers and thus separating them from the rest of the settlement, the fact that all of the towers could only have been accessed by a ramp, etc. All of these similarities indicate specialization and one has to wonder if the possibility exists of a specialized class of tower-builders, travelling from settlement to settlement
Keywords: Archéologie – Oman

Seeking tombs from space - Automatic detection and extraction of Omani burial monuments in satellite images. - Fontana, Giacomo (Leiden University, 2018)
There are thousands of burial monuments in the Sultanate of Oman. Despite some gaps in the cairn sequence, they are among the most consistent evidence of the human occupation between the third millennium B.C.E. and the seventh century C.E. For this reason, they have been used as a proxy for researching the ancient communities that inhabited these territories. Unfortunately, the majority of the extant studies have failed to develop comprehensive and systematic analyses of these tombs. The cause of the current situation is the absence of efficient methods to detect and record the burials. Traditional archaeological surveys cannot provide quantitative data for analysis of large areas. At the same time, the visual interpretation of satellite images is extremely time-consuming and cannot address the changes in archaeological data that have happened during the last decade. Recent developments in remote sensing have aimed to replicate the operation of visual interpretation automatically using computer power. This application has the potential to overcome the issues of the current methodologies used for the detection of the burial monuments of Oman. This project aims to develop an efficient method to detect and record the burial monuments of Oman automatically. This approach allows for the limits of visual interpretation to be overcome and thus to fully exploit the quality and quantity of satellite images currently available. Furthermore, this thesis seeks to go beyond the simple detection of the burials, developing a process aimed at automatically digitalising the tombs. This will allow for the extraction of morphological information that, together with the geographical position of the remains, will allow for the burials to be dated. As a consequence, it will be possible to create rich datasets of tombs suitable for use in addressing current archaeological issues. Furthermore, the automation will also greatly assist in monitoring the status of the remains over time. This is necessary due to ongoing developments and looting activities that threaten the preservation of the tombs. The study and preservation of the burial monuments are indeed urgent issues for the archaeology of the Middle East
Keywords: Archéologie – Oman

Visualizing Fizh: The social implications of the structural properties of an Iron Age ll Omani settlement (1100-600 BC) - Warners, Andy (Leiden University, 2018)
Keywords: Archéologie – Oman

Hafit tombs in the Wadi al-Jizzi and Wadi Suq corridors - Botan, Sam A. (Leiden University, 2019)
This thesis focusses on Hafit tombs (3200-2500 BC) in the Wadi Suq and Wadi al-Jizzi regions of the Sultanate of Oman. The main research question proposed is whether existing theories on the Hafit period can explain the distribution pattern present in the study area. In order to answer this question, four sub-questions were created exploring: the general distribution of the tombs, the orientation of the tombs and the correlation between the tombs, visibility and the dry river beds also known as wadis. Each of the sub-questions was answered by applying different tools in ArcGis on the dataset provided by the Wadi al-Jizzi Archaeological Project. Regarding the overall distribution of the tombs, it can be concluded that significant sites with large numbers of Hafit tombs are primarily located around the Wadi Suq, instead of the larger Wadi al-Jizzi and that all the Hafit cemeteries seem to have been located more closely to the area known as the Lower Batinah than towards the mountains. The analysis also revealed that the tombs at Site 43 seem to be clustered like Late Prehistoric Tombs (LTPs), which are of a post-Hafit date. The orientation of the tombs seemed initially clearly focused towards the north-east/south-west and east-west. This coincides with the variation in the azimuth of the sunrise between the months of June and September for the Sohar region. However, a site-to-site comparison displayed a more nuanced picture. The orientation of the tombs at S6 and S58 are evenly distributed, suggesting that they might have been constructed in a later phase of the Hafit period. The analyses in the current thesis also displayed that at the threshold of 1500 meters all tombs in the study area correlate to a wadi system. Interestingly, all of the tombs are clearly visible from the wadi system, despite the different distances to a wadi. This thesis concludes that current theories are unsatisfactory to explain the distribution of Hafit tombs in the study area and that more research is needed in this regard. Not only to improve existing theories or add new ones, but also to determine whether the patterns discussed in this thesis are unique for the study area or are also visible in other parts of the Oman peninsula.
Keywords: Archéologie – Oman

Practicing Ethnoarchaeology in the Sultanate of Oman - Efstratiou, Nikolaos (On Ibadism, 2014)
Keywords: Archéologie – Oman

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie – Oman

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie – Oman

Chinese porcelains and the decorations of Omani mihrabs - Goffriller, Martin S.; Hongjiao, Ma; Bandyopadhyay, Soumyen; Henderson, Julian (Proceedings of the Seminar for Arabian Studies, 2015)
This paper explores the history of the Chinese porcelain trade in Oman with the aim of gauging the impact of these wares on Oman's religious architecture. The large quantities of porcelain surface finds from the interior and the comparatively unusual reliance on them for the decoration of prayer niches, in the presence of equally valuable wares from Persia and elsewhere, suggest an elevated status for these objects, which is not necessarily a product of their immediate monetary value. Chemical and stylistic analyses were carried out to determine the dates and provenance of the ceramics studied, with the aim of gaining a better understanding of their introduction into the Omani market and their relation to religious design schemes.
Keywords: Archéologie – Oman

Un atelier de potier de la période médiévale découvert à Qalhāt (Oman) - Lesguer, Fabien; Renel, Hélène (Sur les chemins d'Onagre: histoire et archéologie orientales: hommage à Monik Kervran, 2018)
Pionnière de l'archéologie islamique française au Moyen-Orient, Monik Kervran (Cnrs, laboratoire Orient & Méditerranée) s'est illustrée dès le début de sa carrière par ses fouilles à Suse en Iran et la découverte de la statue de Darius en 1972. Elle a dirigé dans les années 70 et 80 la fouille d?importants sites portuaires de la côte arabe du golfe Persique et de la mer d?Oman, à Qal'at al-Bahrain et Sohar. Elle a également mené des recherches en Asie centrale et en Iran oriental, notamment à Nishapour, puis, depuis les années 90, dans le delta de l'Indus où elle a ouvert des fouilles à Sehwan Sharif et Banbhore. 00A travers les dix-neuf contributions internationales présentées dans cet ouvrage, les éditeurs et les contributeurs ont désiré mettre en lumière la diversité des intérêts scientifiques de Monik Kervran. Ils souhaitent ainsi exprimer leur admiration et leur gratitude pour ses apports majeurs aux champs de l'archéologie, de l'histoire, de l'architecture, de l'iconographie et de la culture matérielle du Moyen-Orient et de l'océan Indien occidental aux périodes pré-islamique tardive et islamique
Keywords: Archéologie – Oman